Endogenous political economy: On the inevitability of inefficiency under the natural resource curse - Ana Fernandes (University of Bern, Department of Economics, 2008)
This paper is a first step toward a more fundamental theory of political economy outcomes. We start from the fundamentals of the economy, given by preferences and technology; further, we specify all available technologies for the control of resources - such as armed forces or bribing. We model the interaction of agents in this economy as a game and examine all its equilibria. Equilibrium allocations must be such that individuals maximize their utility and that no group of individuals has the incentive to modify those allocations by (additional) usage of the technologies for the control of resources. The generality of our approach enables us to answer the question 'Is there something about the nature of a country that makes inefficient equilibria inevitable?' We illustrate our approach by applying it to the natural resource curse. The model predicts that inefficient outcomes - in the form of either conflict or a deterrence army solution - will always occur as long as the value of natural resources to capture is positive and the opportunity cost of time - which partly determines soldiers' wages - is finite.
Keywords: H11; O11; P16; 330; endogenous political economy; conflict; deterrence; natural resource curse; inefficiency; general equilibrium